2013
DOI: 10.5923/j.cmaterials.20120206.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Strongly Basic Anion Exchange Resins Tulsion A-30 and Indion-820 by Application of <SUP>131</SUP>I and <SUP>82</SUP> Br as a Tracer Isotopes

Abstract: In the present investigation radioactive tracer isotopes 131 I and 82 Br were used to study the kinetics of iodide and bromide ion-isotopic exchange reaction. The kinetics study was performed to study the effect of ionic concentration and temperature on the specific reaction rate calculated in min -1 . Fro m the initial ionic concentration and knowing the value of specific reaction rate, the values of amount of ions exchanged in mmo l and percentage ion exchange were calcu lated. It was also observed that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The exchange capacity of ion exchange resins was experimentally determined by the standard method [17] using sodium nitrate and titrating against standard silver nitrate solution. Ion exchange resins (0.500 g) in chloride form were equilibrated with iodide ion solution of different concentrations at a constant temperature of 30.0 °C for 3 h. From the results of kinetics study reported earlier [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; it was observed that this duration was adequate to attain the ion exchange equilibrium. After 3 h, the iodide ion solutions in equilibrium with ion exchange resins in chloride form were analyzed for their chloride and iodide ion concentrations by …”
Section: Methodsmentioning
confidence: 99%
“…The exchange capacity of ion exchange resins was experimentally determined by the standard method [17] using sodium nitrate and titrating against standard silver nitrate solution. Ion exchange resins (0.500 g) in chloride form were equilibrated with iodide ion solution of different concentrations at a constant temperature of 30.0 °C for 3 h. From the results of kinetics study reported earlier [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; it was observed that this duration was adequate to attain the ion exchange equilibrium. After 3 h, the iodide ion solutions in equilibrium with ion exchange resins in chloride form were analyzed for their chloride and iodide ion concentrations by …”
Section: Methodsmentioning
confidence: 99%